2002
DOI: 10.1097/00000658-200207000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Postoperative Inflammatory Ileus in the Rat

Abstract: ObjectiveTo investigate local inflammatory events within the colonic muscularis as a causative factor of postoperative ileus. Summary Background DataSurgically induced intestinal muscularis inflammation has been hypothesized as a mechanism for postoperative ileus. The colon is a crucial component for recovery of gastrointestinal motor function after surgery but remains unaddressed. The authors hypothesize that colonic manipulation initiates inflammatory events that directly mediate postoperative smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 33 publications
7
106
0
1
Order By: Relevance
“…The surgical procedure was performed under aseptic conditions. Mice underwent midline laparotomy and colonic manipulation (CM), as described previously (Tü rler et al, 2002). In brief, the colon was exteriorized carefully and then compressed for 5 min by use of sterile moist cotton applicators.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical procedure was performed under aseptic conditions. Mice underwent midline laparotomy and colonic manipulation (CM), as described previously (Tü rler et al, 2002). In brief, the colon was exteriorized carefully and then compressed for 5 min by use of sterile moist cotton applicators.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that inflammatory infiltrates and hypomotility also occur in unmanipulated stomach and colon after standardized jejunal manipulation (72). This propagation of the intestinal inflammation to unmanipulated parts of the gastrointestinal tract has been termed as "gastrointestinal field effect" (FE) (72,83). We also observed FE in rodents after orthotopic small bowel transplantation excluding a spinal or supraspinal reflex (3,80,81).…”
mentioning
confidence: 86%
“…These detrimental alterations are emphasized as major factors in the development of POI (4, 8, 9, 15, 16, 35-38, 40 -42). We reported a time-and trauma-degree-dependent inflammatory cascade (35,36); infiltration of leukocytes (40 -42, 72, 83), macrophages (21,22,37,87), and immunologically competent cells (35,36,40,67,69,72,81,83); and an upregulation of proinflammatory cytokines within the intestinal muscularis (36, 38 -40, 66, 68, 71, 80 -82, 84, 88). The pharmacological or genetic inhibition of macrophages ameliorated the POI in rodents (87,89).…”
mentioning
confidence: 99%
“…17 Animal and human models have suggested that inflammation in the intestinal wall may be directly involved. 18 A consensus conference has reviewed and reported the basic science and some clinical aspects of POI. 19 More details about postulated mechanisms of action and the pathophysiology of POI are presented in subsequent sections.…”
Section: Best Surgical Practice and Investigational Framework For Poimentioning
confidence: 99%